Assessment of community pharmacists’ knowledge, barriers, and practices in detecting antibiotic prescribing errors in Erbil city - Zero Abbas, Awaz; Hassan Ismail , Kameran (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Antibiotic prescribing errors are one of the major contributors to antimicrobial resistance and treatment failure, especially in low-resource places like Erbil, Iraq. This study sought to assess community pharmacists' knowledge in detecting antibiotic prescribing errors, identify the most common types of errors encountered in practice, and explore key barriers that hinder error detection and prevention. Methods: A cross-sectional study was conducted in community pharmacies in Erbil city between November 2024 and March 2025. A structured, self-administered questionnaire was used to collect data from 342 pharmacists selected via convenience sampling. The questionnaire assessed demographics, knowledge, factors that affect prescription errors detection, and types of prescription errors in antibiotics prescription. Results: Data from 342 graduated pharmacists indicated that the workforce is predominantly young, with 74.4% under the age of 30, and largely female (66.8%). The majority were employed in private pharmacies. Only 7.9% demonstrated high knowledge scores regarding antibiotic prescribing errors, the most commonly incorrect responses were related to dosage-related questions. Additionally, 31.2% of participants had received training in antimicrobial stewardship. Statistical analysis showed a significant association between knowledge level and belief in the effectiveness of automated prescribing systems (P = 0.004). A higher proportion of older pharmacists were found in the high knowledge category. Conclusion: The study highlights significant knowledge gaps and limited formal training among community pharmacists regarding antibiotic prescribing errors. Strengthening pharmacist education and implementing structured antibiotic stewardship programs are essential to improving prescribing safety and reducing antimicrobial resistance.